Safety, Tolerability, Pharmacokinetics, and Pharmacodynamics of Domagrozumab (PF‐06252616), an Antimyostatin Monoclonal Antibody, in Healthy Subjects. Issue 5 (7th September 2017) - Bhattacharya, Indranil; Pawlak, Sylvester; Marraffino, Shannon; Christensen, Jared; Sherlock, Sarah P.; Alvey, Christine; Morris, Carl; Arkin, Steven; Binks, Michael
Abstract: Safety, tolerability, anabolic effects, pharmacokinetics, and pharmacodynamics of single ascending and multiple doses of domagrozumab, an antimyostatin monoclonal antibody, were assessed following intravenous (IV) and subcutaneous (SC) administration in healthy subjects. A range of single ascending dose levels between 1 and 40 mg/kg IV and multiple doses (3 doses) of 10 mg/kg IV were tested (n = 8 per cohort). Additionally, a 3 mg/kg SC (n = 8) cohort also received domagrozumab. Magnetic resonance imaging and whole‐body dual‐energy x‐ray absorptiometry imaging were conducted to investigate the anabolic effects of domagrozumab. Domagrozumab was well tolerated with no severe and 1 non–treatment‐related serious adverse event. The most commonly reported adverse events were headache (21 subjects) and fatigue, upper respiratory tract infections, and muscle spasms (10 subjects each). Domagrozumab demonstrated typical IgG1 pharmacokinetics, with slow SC absorption and slow clearance, low volume of distribution, and a long half‐life. Target engagement was observed with an increase in extent of myostatin modulation, plateauing at the 20 mg/kg IV dose. Downstream pharmacology following myostatin binding by domagrozumab was only observed in the 10 mg/kg single IV cohort (increase in whole‐body lean mass of 5.38% using dual‐energy x‐ray absorptiometry) and the 10 mg/kg repeat‐dose cohort (muscle volume increase of 4.49% using magnetic resonance imaging).